Diversifying molecular and topological space via a supramolecular solid-state synthesis: a purely organic mok net sustained by hydrogen bonds. (2019) - Oburn, Shalisa M.; Sinnwell, Michael A.; Ericson, Devin P.; Reinheimer, Eric W.; Proserpio, Davide M.; Groeneman, Ryan H.; MacGillivray, Leonard
No abstract available